THE EFFECT OF ENTREPRENEURIAL SELF-EFFICACY, ENTREPRENEURIAL ATTITUDES AND THE USE OF SOCIAL MEDIA ON SMES PERFORMANCE - Suheryanto, Fadillah Akbar; Ie, Mei (International Journal of Application on Economics and Business, 2023)
The purpose of this study is to determine the impact of entrepreneurial self-efficacy, entrepreneurial attitudes and the use of social media on the performance of SMEs. The population used in this study is the owner of a small and medium culinary business in the Kelapa Gading area. The number of samples used for this study were 50 respondents using non-probability sampling for data collection and using a purposive sampling technique whose criteria were Small and Medium Culinary Enterprises in the Kelapa Gading area. The design of this research is descriptive cross-sectional because the data collection in this study uses field information, due to the data in this study using the SmartPLS version 3.3.3 application. What will happen is that this research states that entrepreneurial behavior does not have a significant effect on the performance of SMEs, while entrepreneurial self-efficacy and the use of social media have a positive and significant impact on the performance of SMEs. In the future, this research can help small and medium business owners to be able to use social media to run their business. And this research can also help increase the awareness of business owners that having self-efficacy in oneself and also mastering entrepreneurial attitudes is an important thing and can affect the business being run.